Women's and men's responses to in-work benefits: The influence of children - Daniela Andrén; Thomas Andrén (IZA Journal of Labor Policy, 2016)
This study examines how the Swedish earned income tax credit (EITC) introduced in 2007 affected the labor supply of men and women living in two-adult households and the extent to which children in the household affected the outcome. Because the EITC is non-targeted in Sweden, it is difficult to form a meaningful comparison group for a regular ex-post quasi-experimental evaluation of the reform. Therefore, a structural discrete choice labor supply model for two-adult households is formulated and used in an ex ante analysis. In a first step, estimates from the structural labor supply model are used to determine the wage elasticities of the labor supply of men and women separately, both with and without children in the household. Our results correspond to those previously reported in the academic literature: somewhat larger wage elasticities are found for women than for men, while similar labor supply responses are found for men and women when there are no children in the household. In a second step, the labor supply model is used to simulate the labor supply responses to the EITC. Our results indicate that the largest response is on the extensive margin, with an increase in the labor force participation of both men and women. While the labor supply effect on the intensive margin is smaller, it is positive for both men and women working part-time. However, the presence of children affects work hours differently for men and women working part-time or not at all. For men, the percentage change in the work hours was much higher for those living in a household without children, whereas for women, the changes are almost the same for the two types of households.
Keywords: J21; H24; 330; Structural discrete labor supply model; EITC; Younger children; Two-adult households